An evo-devo perspective on the regeneration patterns of continuous arm structures in stellate echinoderms. Issue 1 (31st December 2022) - Allievi, A.; Canavesi, M.; Ferrario, C.; Sugni, M.; Bonasoro, F.
Abstract: Regeneration is a post-embryonic developmental process common in Metazoa, which, despite obvious taxa-specific differences, can often share common principles and patterns. Among these, the distalization and (proximal) intercalation model successfully describes most animal regeneration phenomena. Stellate echinoderms (Crinoidea, Asteroidea, and Ophiuroidea) are particularly practical models for regeneration studies as the proximo-distal regrowth of their "segmental" arms, including the inner "continuous" yet homologous structures, i.e . radial water canal, radial nerve cord, and somatocoel, provide a unique opportunity to investigate the existence of evolutionarily shared regenerative patterns. In the present work, we comparatively examined the anatomy of arm regeneration in four stellate echinoderm species – the crinoid Antedon mediterranea, the asteroids Echinaster sepositus and Coscinasterias tenuispina, and the ophiuroid Amphipholis squamata . We observed that in all the models the distal elements, i.e. the apical blastema of crinoids, and terminal ossicle and tube foot of asteroids and ophiuroids, form in an early stage, followed by the proximal region, which develops in the proximal-to-distal direction. In all arms, the continuous structures develop before discrete lateral structures (e.g. ossicles and tube feet), and appear to provide materials that make the subsequent development possible. Overall, the model inferred from our study is compatible with those previously proposed for other animal models that involve processes of distalization and intercalation. The evidence of shared patterns suggests that at least some overall regeneration mechanisms have ancient origins and are well conserved throughout echinoderm and animal evolution. This study could help shed light on those evolutionarily conserved principles (patterns) among metazoan regeneration.